2014
DOI: 10.1016/j.cll.2014.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Infections in Patients with Cystic Fibrosis

Abstract: Survival has improved in patients with cystic fibrosis (CF), in part because of aggressive antimicrobial management. Two multidrug-resistant environmental bacteria, the Burkholderia cepacia group and nontuberculous mycobacteria, have emerged. Improving genomic and proteomic technologies are allowing better identification of bacteria and fungi found in the CF lung and detection of viral agents that may be associated with pulmonary exacerbations. Anaerobic bacteria and Streptococcus angionsus group organisms may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
60
1
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 108 publications
0
60
1
9
Order By: Relevance
“…Staphylococcus aureus , Pseudomonas aeruginosa , Burkholderia cepacia and Haemophilus influenzae ), filamentous fungi and/or yeasts. NTM infections are increasingly being reported in adults with CF , but children are also vulnerable . The frequency of NTM infections in CF children from the UK has been estimated at 3.3% .…”
Section: Inherited Conditions Affecting the Lungs And Conferring A Prmentioning
confidence: 99%
“…Staphylococcus aureus , Pseudomonas aeruginosa , Burkholderia cepacia and Haemophilus influenzae ), filamentous fungi and/or yeasts. NTM infections are increasingly being reported in adults with CF , but children are also vulnerable . The frequency of NTM infections in CF children from the UK has been estimated at 3.3% .…”
Section: Inherited Conditions Affecting the Lungs And Conferring A Prmentioning
confidence: 99%
“…Cystic fibrosis (CF) is characterized by chronic microbial infections within the lower respiratory tract (Gilligan, 2014;LiPuma, 2010). It is now well established that the CF airways harbour a complex microbiota in addition to classical pathogens, including Pseudomonas aeruginosa, Staphylococcus aureus, Haemophilus influenzae and the Burkholderia cepacia complex (Dickson et al, 2013;Lynch & Bruce, 2013;Rabin & Surette, 2012;Rogers et al, 2015;Surette, 2014), and diverse commensal streptococci (LiPuma, 2012;Lynch & Bruce, 2013;Rogers et al, 2010;Sibley et al, 2006), some of which may become pathogenic (Parkins et al, 2008;Sibley et al, 2008aSibley et al, , 2009Sibley et al, , 2010.…”
Section: Introductionmentioning
confidence: 99%
“…P. aeruginosa is considered the main bacterium that affects people with CF, causing chronic lung infections, which leads to high rates of morbidity and mortality, and once the bacteria is established, it is difficult to eradicate it (Winstanley et al, 2016). On the other hand, patients colonized in a chronic manner with B. cepacia present a worse prognosis of the disease, as the use of antibiotics becomes more frequent they also have a greater deterioration of lung function and the rate of mortality is higher compared to that patients colonized by only P. aeruginosa (Gilligan, 2014; Folescu et al, 2015). It has been reported that B. cepacia and P. aeruginosa can form mixed biofilms in the lungs of people with CF, since, P. aeruginosa through its extracellular products can increase the attachment of B. cepacia by modifying the lung epithelial cells on its surface; however, the same does not occur in patients previously colonized with B. cepacia (Saiman et al, 1990).…”
Section: Nets Formation By Microorganisms Of Cystic Fibrosismentioning
confidence: 99%